Public Trust in News Disseminated by Government Banks: Basra Banks as a Case Study - Ali Falih Dakhil Al-Karim; Mohammed Rashid Majeed (Genius Journals, 2025)
In today's world, government banks and their affiliated media outlets are the primary sources of communication and financial information for the public. Public trust in the news disseminated by government banks is of paramount importance and can have farreaching effects on the economy and financial decisions. Therefore, the main purpose of this research is to study public trust in the news disseminated by government banks, using banks in the city of Basra as a case study. To answer the research questions, the researcher developed a questionnaire for the research variable. To achieve the research objectives, a quantitative research method was used, and the questionnaire was distributed to a sample of (408) individuals from the city of Basra. To define the research objectives, the researcher used a set of statistical methods, including Cochrane's equation to determine the appropriate sample size, Cronbach's alpha to verify the reliability of the questionnaire, and Spearman's and Student's t-tests to test the research hypotheses. This research reached the following conclusions: At a 95% confidence level, public trust in news disseminated by government banks in Basra is above average. Furthermore, testing the sub-hypotheses revealed a positive correlation between the two variables; that is, the higher the degree of truthfulness of the news disseminated by government banks, the higher the degree of trust among the public in Salah al-Din Governorate. Similarly, a positive correlation exists between these two variables; that is, the higher the degree of bias towards the news disseminated by government banks, the higher the degree of trust among the public in Salah al-Din Governorate. Also, a positive correlation exists between these two variables; that is, the higher the degree of appeal of the news disseminated by government banks, the higher the degree of trust among the public in Salah al-Din Governorate. Among the most important recommendations of the researcher is: Forming expert teams: To ensure the accuracy of financial and economic news, government banks should form impartial expert teams. These teams would analyze the news and verify its accuracy, and they would not have any financial or political guarantees. Conflict of Interest Management: State-owned banks should establish policies and procedures to manage conflicts of interest in news reporting. Individuals involved in news reporting should not have personal interests influencing their decisions. Multimedia Utilization: State-owned banks should utilize multimedia platforms such as websites, social media, and podcasts to engage audiences. These diverse channels can make news more appealing
Keywords: Trust; Honesty; Impartiality; Appeal